2009
DOI: 10.1111/j.1464-5491.2009.02814.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum apolipoprotein C‐III in high‐density lipoprotein: a key diabetogenic risk factor in Turks

Abstract: Serum total apoC-III or its fractions are linearly and inversely associated with smoking, positively with alcohol usage and serum complement C3. The presumably dysfunctional HDL apoC-III is a stronger predictor of Type 2 diabetes than waist girth in Turks. Non-HDL apoC-III predicts strongly the development of MetS as well as incident CHD, independent of HDL cholesterol, BMI and non-lipid factors. The atherogenicity of apoC-III and dysfunctionality of HDL apoC-III carry huge public health implications in Turks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 29 publications
6
36
0
2
Order By: Relevance
“…In addition, the development of MetS and diabetes was predicted by apoA-II concentrations, irrespective of HDL-cholesterol concentrations. This phenomenon is consistent with previously demonstrated cardiometabolic risk conferred by similar functional alterations in HDL (17), apoA-I (15), apoC-III in HDL (18) and in adiponectin (29) in the TARF cohort.…”
Section: Manifestations Of Impaired Anti-inflammatory/ Anti-oxidativesupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, the development of MetS and diabetes was predicted by apoA-II concentrations, irrespective of HDL-cholesterol concentrations. This phenomenon is consistent with previously demonstrated cardiometabolic risk conferred by similar functional alterations in HDL (17), apoA-I (15), apoC-III in HDL (18) and in adiponectin (29) in the TARF cohort.…”
Section: Manifestations Of Impaired Anti-inflammatory/ Anti-oxidativesupporting
confidence: 80%
“…However, recent prospective analyses in the TARF showed that increased serum apo A-I was diabetogenic and tended to be atherogenic among Turks (15). In addition, increased concentrations of adiponectin (16), HDL-cholesterol (17) and apoC-III in HDL (18) showed similar effects. The abnormal func-tions of these normally protective serum proteins have been proposed to result from an environment of atherogenic dyslipidemia, excessive oxidative stress and systemic low-grade inflammation associated with the high prevalence of MetS among Turks (19).…”
Section: Introductionmentioning
confidence: 71%
“…We studied the distribution of these different apolipoproteindefi ned HDL types in a group with normal HDL-C levels and normal body weight and compared it with that of an obese group, a common high-risk phenotype associated with low HDL-C. Elevated apoC-III concentrations in HDL ( 34,35 ), as well as increased apoC-III production ( 36 ), are common features of obesity. We hypothesized that the distribution of HDL particles is disturbed with obesity, such that obese subjects have higher concentrations of HDL with apoC-III as well as HDL with apoE, and lower concentrations of HDL without apoE or apoC-III contributing to their increased risk for CHD.…”
Section: Isolation Of Hdl From Plasma By Immunoaffi Nity Chromatographymentioning
confidence: 99%
“…Total and LDL-cholesterol tended to be lower in the CHD group and LDL-cholesterol tended to be inversely associated with CHD, while apoB levels were significantly and positively associated with CHD likelihood. These findings suggest that HDL-apoCIII may assume atherogenic properties (just as it was shown in 2008 by us [10] to assume diabetogenic properties) in an environment of low LDLcholesterol (and high apoB), consistent with autoimmune involvement of Lp(a) protein, but not of apoB. Moreover, of interest is the finding of…”
Section: Individual Plasma Proteins Epidemiologically Identified As Hmentioning
confidence: 64%